Assume you have $A(L)y_t = B(L)e_t$ and $e_t$ is a zero mean white noise with variance $\sigma^2$. Why is the long-run variance of $y_t$ equal to $\sigma^2\left(\frac{B(1)}{A(1)}\right)^2$?

I know that the long-run variance is the infinite sum of all autocovariances of $y_t$ and that it can also be written as: $\gamma(0) + 2\sum_{j=1}^{\infty}\gamma(j)$ where $\gamma(0)$ is variance of $y_t$ and $\gamma(j)$ is j-th autocovariance $Cov(y_t,y_{t-j})$. But I struggle to reach this form $\sigma^2\left(\frac{B(1)}{A(1)}\right)^2$.


1 Answer 1


By definition, the long-run variance is the infinite sum of all autocovariances of $y_t$:

$LRV(y_t) = \sum_{k=-\infty}^{\infty} \gamma_{j}$

Rewrite $y_t$ in its Wold representation: $y_t = A^{-1}(L)B(L)e_t = \Psi(L) e_t$,


$\sum_{k=-\infty}^{\infty} \gamma_{j} = \sum_{k=-\infty}^{\infty} COV(\sum_{i=0}^{\infty}\psi_i e_{t-i},\sum_{j=0}^{\infty}\psi_j e_{t+k-j}) = $

$\sum_{k=-\infty}^{\infty} \sum_{i=0}^{\infty} \sum_{j=0}^{\infty} \psi_i \psi_j COV(e_{t-i},e_{t+k-j}) =$

$\sigma ^2 \sum_{k=-\infty}^{\infty} \sum_{i=0}^{\infty} \sum_{j=0}^{\infty} \psi_i \psi_j I(t-i = t + k - j) =$

$\sigma ^2 \sum_{k=-\infty}^{\infty} \sum_{i=0}^{\infty} \psi_i \psi_{k+i} =$

$\sigma ^2 \sum_{i=0}^{\infty} \sum_{k=-i}^{\infty} \psi_i \psi_{k+i} =$

$\sigma^2 (\sum_{i=0}^{\infty} \psi_i)^2 =$

$ \sigma^2 \psi(1)^2 = $

$\sigma^2 \frac{1+b_1 + ... + b_q}{1 - a_1 - ... - a_p} =$

$ \sigma^2 (\frac{B(1)}{A(1)})^2 $

  • $\begingroup$ Thank you for your answer, it is obviously helpful for the LRV of general linear processes, too. Could you elaborate on what you did in step 4 to 5? To be more precise, why does the starting index of the sum change when interchanging the sums? $\endgroup$ Sep 23, 2019 at 10:35
  • 4
    $\begingroup$ If we take the unconditional variance for $AR(1)$ then it is given by $\gamma(0) = \sigma^2 / (1 - a_1^2)$ which doesn't seem to agree with this formula. Is this LVR the same as the unconditional variance of a stationary process or is it something else? Thank you $\endgroup$
    – Confounded
    Nov 15, 2020 at 15:03
  • $\begingroup$ Indeed. What are $b_1,\dots,b_q$ and $a_1,\dots,a_p$? $\endgroup$ Feb 1, 2021 at 15:02
  • $\begingroup$ This answer stats.stackexchange.com/a/471296/234732 would point to this answer being incorrect. $\endgroup$ Oct 3, 2022 at 19:50
  • $\begingroup$ I believe where this answer goes wrong is in asserting $\sum \psi_i^2=(\sum \psi_i)^2$ $\endgroup$ Oct 3, 2022 at 20:01

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.